IMPACT THE PURSUIT OF GLOBAL EDUCATION AMONG VIETNAMESE STUDENTS: FINDING AND DISCUSSION - Tri, Nguyen Minh (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2023)
Pursuing education abroad has become popular among Vietnamese students for personal growth, financial stability, and career advancement. However, the decision to study abroad is not purely based on individual or familial choices. External factors such as cultural, social, economic, political, foreign relations, and educational factors within Vietnam also play a significant role. Through an analysis of relevant studies and literature, this paper provides valuable insights into the dynamics contributing to the increasing trend of Vietnamese students transitioning towards international education.